Preliminar study on bioactive potential of Annona cherimola (anona) and Prunus domestica (ciruelo) cultivated in Costa Rica - Navarro-Hoyos, Mirtha (2014)
The nutritional and health benefits of bioactive metabolites such as alkaloids, triterpenes and more recently of polyphenols have increased at international level the intake of natural products that constitute potential sources of such compounds as well as the importance of structural characterization in correlation with their bioactivity. The present research involved the study of fruit species Annona cherimola (cherimola) and Prunus domestica (plum) cultivated in Costa Rica due to their traditional use related to their antioxidant potential and also based on results of international studies that demonstrated the health benefits of polyphenols in relation to cardiovascular diseases, anti-inflammatory, anticancer, neuroprotective and antimicrobial activity as well as the fact that due to the antioxidant effects against oxygen reactive species, these fruits have been included as functional ingredients in nutritional supplements. Plants from both species were located, fruits were collected and after due processing laboratory analysis was undertaken on polyphenol contents and bioactivity. Cuttings were extracted for vegetative reproduction and were planted in Cabuyal of San Pedro at Poas, Alajuela (Green Ladies) and Llano Bonito at León Cortés, San Jose (PROAL), where collaborative work was performed with organized groups of women located in these communities, who elaborate artisan cosmetic products such as shampoos, creams and ointments with medicinal plants ingredients; contributing to their capacity building through training in the importance of germplasm conservation as well as in good production practices.